Sistem Informasi Situs Purbakala Di Jawa Timur Berbasis Web - Sasangka, Haditya Wahyu; Wibowo, Januar; Taufik, Vicky M. (Jurnal JSIKA, 2012)
There are many ancient objects that less handled by government,so the information about position and culture preserve site history is truly minus. This condition make people not interested again with culture preserve site, that something one can make Indonesia proud last time. Web based geographic information system that make it easier to analyzed the position of ancient sites in east java. SIG application and Google Map API that integrated with djikstra algorithms can gived information about position of culture preserve that nearest with the user. Every single step have been choosed are minimum in every side that entered to compilation solution,is greedy principle that applied by djikstra algorithms. System ability to found shortest route can facilitate user to find shortest location from user domicile to culture preserve which one they want to go.” Keywords: Culture Preserve, SIG, Djikstra.